Penerapan Model Belajar Mengajar Word Square terhadap Keaktifan Peserta Didik di MI Al Falah - Hasan , Efvysien Nur (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAI Senori Tuban, 2023)
One of the processes of good teaching and learning activities is determined by the activeness of students. The way to increase student activity significantly and comprehensively is that teachers are required to use learning strategies that are tailored to the needs of elementary school students and individual characteristics and create a comfortable and enjoyable learning atmosphere. One interesting learning model that improves the quality of learning and can influence student activity is the learning model word square. Learning model word square is a learning model that requires students' astuteness and precision to find the words in the box by combining the questions and answers in the box. This type of research is classroom action research (Classroom Action Research) carried out in two cycles. Results of the analysis of student activity in cycle I and cycle II with the application of the learning model word square show that the level of student activity in cycle I was 55.66% for Medium criteria and in cycle II it increased to 80.33% for High criteria. The results of this research prove that there is an enhancement in students' learning activity after implementing the model learning word square carried out by the teacher. Thus it can be concluded that the application of the learning model word square can increase the learning activity of class V students of class V Madrasah IbtidaiyahAl Falah Semester I of the 2023/2024 Academic Year in Natural and Social Sciences (IPAS) subjects.